A modified exergy analysis method for vapor compression systems: Splitting refrigerant exergy destruction. (25th January 2022) - Cui, Mengdi; Wang, Baolong; Wei, Falin; Shi, Wenxing
Highlights: An exergy analysis method for splitting refrigerant exergy destruction is proposed. Heat pump water heater optimized by the proposed method improves COP by 17.0–27.5%. Refrigerant exergy destruction ratio is about 20% for low-frequency air conditioner. Reducing compressor and refrigerant exergy destructions is key for air conditioner. Abstract: To locate the major imperfections and determine the optimization directions for developing high-efficiency vapor compression systems, a modified exergy analysis method is proposed in this study. In contrast to previous exergy analysis methods, the proposed method can split the exergy destruction of the refrigerant and simultaneously exhibit exergy destructions of the refrigerant and other components, which makes the optimization more effective. The modified exergy analysis is compared with other exergy analysis methods by analyzing and optimizing an air source heat pump water heater. As a result, the optimization of a typical air source heat pump water heater based on the modified exergy analysis method achieves a coefficient of performance improvement of over 17.0–27.5% compared to other exergy analysis methods. Finally, the modified exergy analysis method is used to optimize an actual high-efficiency inverter room air conditioner. The optimization directions are clarified. Improving the energy efficiency of the compressor and decreasing the refrigerant exergy destruction are identified to be the key factors for optimization.